ANALYSIS OF SCIENTIFIC ATTITUDE REVIEWED BY GENDER OF STUDENTS CLASS VIII of A ACCREDITATED STATE SMP in SOMBA OPU SEQUENCES - Vira Virginia; Salma Samputri; Muh Tawil (Jurnal IPA Terpadu, 2024)
This study analyzes the scientific attitudes of VIII grade students in Public Junior High School Accredited “A” in Somba Opu District. This research is descriptive quantitative with a population of 1481 students and a sample of 527 students which 258 male students and 269 female students were randomly selected. The research instrument was a scientific attitude questionnaire consisting of 46 statement items. The conclusion results show:  1) The average score of student’s scientific attitude that obtained is 141.69, with an average male score of 140.49 and an average female score of 142.87. 2) The average percentage score of the scientific attitude dimension of men is 76% with a moderate category and women are 78% with a moderate category. 3) The estimated average population score range is 141-143 with a moderate category, for the male gender the score range is 139-141 with a moderate category and the female gender score range is 142-144 with a moderate category. 4) There are differences in scientific attitudes in terms of gender of students in class VIII of A-qualified public junior high schools in Somba Opu sub-district.